Evaluation of Chitosan Modified by Acidic Deep Eutectic Solvents in the Extraction of Flavonoids from Sea Buckthorn (Hippophae Rhamnoides L.) Leaves. (11th February 2022) - Dai, Yunliang; Row, Kyung Ho
Abstract: Eight deep eutectic solvents composed of choline chloride and various acids were used to synthesize chitosan derivatives. All acidic deep eutectic solvents resulted in high transmittance and stable chitosan derivatives under the appropriate reaction conditions. Choline chloride–oleic acid–chitosan provided the best performance and was used for the ultrasound-assisted extraction of rutin, quercetin, and isorhamnetin from sea buckthorn ( Hippophae rhamnoides L. ) leaves coupled with reversed-phase high-performance liquid chromatography (RP-HPLC). The extraction provided recoveries of 107.5 ± 0.16 rutin, 30.22 ± 0.37 quercetin, and 43.5 ± 0.22 isorhamnetin mg g −1  dry powder using the optimal conditions at 41 °C, solid/solvent ratio of 1:24 g mL −1, and six adsorption/desorption cycles. The linear range was from 1.0 to 1000.0 µg mL −1 and the limits of detection (LODs) for rutin, quercetin, and isorhamnetin were 0.12, 0.16, and 0.23 µg g −1, respectively. The results showed that sea buckthorn ( H. rhamnoides L. ) leaves, a food industry by-product, may be used as an inexpensive source of flavonoids.